2017
DOI: 10.1002/star.201700141
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and antioxidant activity of caffeic‐acid‐grafted corn starch

Abstract: The antioxidant molecule of caffeic acid was grafted onto corn starch by an N,N 0 -carbonyl diimidazole-mediated reaction. The structural, crystalline, thermal, and antioxidant properties of caffeic-acid-grafted starch (caffeic acid-g-starch) were investigated. The grafting ratio of caffeic acid-g-starch was determined as 66.1 mg/g by the Folin-Ciocalteu method. The Fouriertransform infrared spectrum of caffeic acid-g-starch exhibited a band at 1720 cm À1 attributed to the vibration of the esterified carboxyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…The weight loss of the third and fourth stages, might be due to decomposition of SI residues, and decomposed SI molecules need a period of time to reach a constant weight, so that the mass loss slowly (Zhang et al, 2011). high decomposition temperature proves stronger thermal stability (Liu & Wang, 2017). In this study, the thermal stability of starch was improved after adding soy isoflavone.…”
Section: Thermogravimetric Analysis Of Cs-si Complexesmentioning
confidence: 76%
See 1 more Smart Citation
“…The weight loss of the third and fourth stages, might be due to decomposition of SI residues, and decomposed SI molecules need a period of time to reach a constant weight, so that the mass loss slowly (Zhang et al, 2011). high decomposition temperature proves stronger thermal stability (Liu & Wang, 2017). In this study, the thermal stability of starch was improved after adding soy isoflavone.…”
Section: Thermogravimetric Analysis Of Cs-si Complexesmentioning
confidence: 76%
“…Compared with SSI‐0, decomposition temperature of CS‐SI complexes increased from 315°C to 320°C. The decomposition temperature of starch is related to its crystal type, processing method, chemical modification, and relative molecular mass, and high decomposition temperature proves stronger thermal stability (Liu & Wang, 2017). In this study, the thermal stability of starch was improved after adding soy isoflavone.…”
Section: Resultsmentioning
confidence: 99%
“…During coffee production, spent coffee ground (SCG) is generated as a major waste . SCG has been used for various applications that is, production of active carbon, reinforcing phase in polymer composite and raw material for antioxidant extractions . Yen et al reported that roasted coffee residue extracted by water showed the highest yield of antioxidants for protection of lipid per oxidation compared with other organic solvents.…”
Section: Introductionmentioning
confidence: 94%
“…[13] SCG has been used for various applications that is, production of active carbon, reinforcing phase in polymer composite and raw material for antioxidant extractions. [14][15][16][17][18] Yen et al [19] reported that roasted coffee residue extracted by water showed the highest yield of antioxidants for protection of lipid per oxidation compared with other organic solvents. The components of extracted roasted coffee residue consisted of both phenolic compound including chlorogenic acid and caffeic acid as well as non-phenolic compound namely caffeine, trigonelline, nicotinic acid, and 5-(hydroxymethyl)-2-furfuraldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…The copolymers of carbohydrate polymers, e.g., starch, cellulose, dextran, carboxymethylcellulose, lignocellulose, alginate, chitosan, etc. and various structure vinyl monomers, e.g., styrene, methacrylates, acrylates can be synthesized . In addition, the graft copolymers of synthetic polymers such as (poly(chloroethyl vinyl ether)‐g‐polystyrene)comb‐b‐(poly(chloropyran ethoxy vinyl ether)‐g‐polyisoprene)comb, (meth)acrylate copolymer grafted with long fluorinated side chain, Nylon 6‐g‐poly(acrylic acid), polyethylene‐g‐poly(acrylic acid), polyaniline‐g‐(sulfonated polyurethane), poly(N‐vinylpyrrolidinone‐g‐styrene), etc.…”
Section: Introductionmentioning
confidence: 99%